Audiometric Findings in Senior Adults of 80 Years and Older - De Raedemaeker, Kaat; Foulon, Ina; Vella Azzopardi, Roberta; Lichtert, Elke; Buyl, Ronald; Topsakal, Vedat; Beyer, Ingo; Bautmans, Ivan; Michel, Olaf; Gordts, Frans (Frontiers in Psychology, 2022)
Objective: To examine hearing thresholds in senior adults of 80 years and older and compare this data to the current ISO 7029 reference values. Design: A descriptive, prospective study testing pure-tone and speech audiometry in senior adults participating in the BUTTERFLY study or the BrUssels sTudy on The Early pRedictors of FraiLtY. A Gerontological study to identify determinants for active aging and for early stages of frailty in the oldest population. Using the formula given by ISO 7028:2017 the median value of hearing was calculated based on the sex and age of the participant and compared to the measured hearing thresholds. Results: 151 senior adults were included. The prevalence of hearing loss was 90.7% (PTA > 20 dB HL). The results were compared to the mean ISO values, calculated for every participant. Both males and females in our study population had worse hearing thresholds than could be expected based on the ISO reference values. In our study population with moderate hearing loss (PTA > 40 dB HL), 38% is underserved in term of hearing restoration healthcare and yet another 38% is unsatisfied with the result of the hearing aids. Given the vast impact on the individual and society, this is a problem in need of our attention. Conclusion: The ISO 7029 reference values may be an underestimation of hearing loss in senior adults of 80 years and older. Therefore we present a statistical distribution of hearing thresholds on different frequencies related to age and sex that can be used as a baseline for further development of the reference values.